1997
DOI: 10.1017/s0140525x97000010
|View full text |Cite
|
Sign up to set email alerts
|

What memory is for

Abstract: Let's start from scratch in thinking about what memory is for, and consequently, how it works. Suppose that memory and conceptualization work in the service of perception and action. In this case, conceptualization is the encoding of patterns of possible physical interaction with a three-dimensional world. These patterns are constrained by the structure of the environment, the structure of our bodies, and memory. Thus, how we perceive and conceive of the environment is determined by the types of bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
796
0
26

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,354 publications
(888 citation statements)
references
References 203 publications
66
796
0
26
Order By: Relevance
“…For example, ventral premotor cortex and posterior parietal cortex were previously implicated in motor representations associated with tool usage [Chao and Martin, 2000;Culham et al, 2006;Phillips et al, 2002]. The inclusion of motor and somatosensory areas in object representations is also consistent with ''embodied cognition,'' a theoretical position holding that conceptual representations contain perceptual and motor components corresponding to human interactions with real entities in the physical environment (e.g., Glenberg, 1997]. There are multiple brain regions, besides classical object-selective cortex that contain information about the object category.…”
Section: Conclusion and Discussionmentioning
confidence: 60%
“…For example, ventral premotor cortex and posterior parietal cortex were previously implicated in motor representations associated with tool usage [Chao and Martin, 2000;Culham et al, 2006;Phillips et al, 2002]. The inclusion of motor and somatosensory areas in object representations is also consistent with ''embodied cognition,'' a theoretical position holding that conceptual representations contain perceptual and motor components corresponding to human interactions with real entities in the physical environment (e.g., Glenberg, 1997]. There are multiple brain regions, besides classical object-selective cortex that contain information about the object category.…”
Section: Conclusion and Discussionmentioning
confidence: 60%
“…Memory is a system created by natural selection (e.g., Glenberg, 1997;Howe, 2011;Klein, Cosmides, et al, 2002;Nairne, 2005;Sherry & Schacter, 1987): It exists in its present form because that arrangement solved certain recurrent problems faced by the organism in its evolutionary past. Evolution does not produce new, complex, metabolically costly phenotypic systems by chance (Dawkins, 1976;Mayr, 2001;Williams, 1966).…”
Section: The Functional Aspects Of Memorymentioning
confidence: 99%
“…In other words we avert our gaze at critical points within a task or interaction to avoid processing of unnecessary, distracting or arousing visual cues from our environment. Glenberg (1997) proposed a model of cognition in line with the cognitive load hypothesis. He Development of Gaze Aversion 4 suggested that the cognitive system is normally "clamped" to the environment, and so we are constantly processing environmental events.…”
Section: Visual Communication Signals and Cognitive Effortmentioning
confidence: 99%